Biotemplating : complex structures from natural materials - Hall, Simon R. (Imperial College Press, 2009)
In terms of structural complexity, the natural world presents innumerable examples of stunning beauty and high functionality, usually with the minimum of material and energy expenditure. Materials chemists can harness these amazing structures as ready-made scaffolds on which to grow inorganic phases which replicate the underlying complexity, thereby producing materials with greatly enhanced physical properties. This book comprehensively describes the entire range of natural materials that have been used in this way and the inorganic phases which result from them. The book covers simple molecul.
Keywords: Bioengineering.; Biomolecules.; Macromolecules.; Biotechnology.; elektronické knihy; electronic books